Despicable Deviants: Labelling Theory and the Polemic of the Pastorals - Pietersen, Lloyd (Sociology of religion, 1997)
The paper proposes that an adequate historical-critical understanding of the Pastoral Epistles — 1 Timothy, 2 Timothy, and Titus — can be advanced by using sensitizing concepts from the labelling theory variant of symbolic interactionism. In the three epistles, the technique of the “status degradation ceremony” is seen to transform previously influential Christian insiders into outsiders.